The Impact of the Covid-19 Virus on the Development of Micro, Small and Small Enterprises (MSEs) Partners of LPPM Untag Surabaya - Ayun Maduwinarti; Sri Andayani (Institute of Computer Science (IOCS), 2021)
The corona virus that is spreading in several countries including Indonesia has a very significant impact on social and economic life, this is because the impact of the virus can cause death, and this has been found in several provinces in Indonesia. The impact of this virus is very influential on the national economy, including the existence of Micro and Small Enterprises (MSEs). Likewise, what has happened to MSEs that have become LPPM Untag Surabaya Partners. UMKs who have become LPPM Partners include those who are doing business in the fields of batik, handicrafts, food and beverages and others. UMK which became the respondents in this study were: 1. Teyeng Batik UMK, 2. Kartini Bordi UMK, 3. Kanta Craft UMK, 4. ESM Collection UMK, 5. Cassava UMK, 6. Delicious UMK. The title of this research is the Impact of the Covid-19 Virus on the Development of Micro, Small and Small Business Partners of Lppm Untag Surabaya. Problems in research: How is the impact of Covid-19 on the Business Activities (UMK) of LPPM Untag Surabaya Partners and how these MSEs overcome the problem. Research objectives: 1. To find out how the condition of Covid-19 has an impact on the business activities of UMK Partners LPPM Untag Surabaya. 2. How can UMK partners of LPPM Untag Surabaya solve the problem. Research Outcomes: 1. Research reports that can be used as input for SMEs LPPM Partners in running their business, 2. Scientific journals with ISSN or accredited journals / SINTA. The research method used is descriptive qualitative method. The results showed that the Covid-19 pandemic had a tremendous impact on the development of the MSEs of the LPPM partners under study, namely:the average decreased up to 90%. Meanwhile, MSEs for food products decreased by 70%. 2. All MSEs maximize their online sales by using social media such as Facebook, Instagram, WhatsApp. The solution made by most of the LPPM partner MSEs shifted their business by making masks, food and taking orders outside of their usual business.